Effect of Stimulation on the Stabilization of Platelet-Fibrinogen Interactions - Peerschke, Ellinor I B (Thrombosis and Haemostasis, 1992)
The interaction between fibrinogen and stimulated platelets is a multiphasic process that culminates in the stabilization of ligand binding and reduced accessibility of bound fibrinogen to exogenous antibody. The present study was designed to further explore platelet-fibrinogen interactions by examining the effect of agonist on bound fibrinogen expression and interaction with stimulated platelets as a function of time after ligand binding. Two agents were identified, Zn2+ and phorbol myristate acetate (PMA), which support progressive decreases in bound fibrinogen expression on platelets, but fail to support the stabilization of fibrinogen binding. Sixty min after binding to platelets, approximately 80% of bound fibrinogen remained reversibly associated with Zn2+- or PMA-treated platelets and failed to associate with the Triton X-100 insoluble cytoskeleton. In contrast, polyclonal anti-fibrinogen antibody binding decreased by more than 66%. Over the same time course, fibrinogen binding to control platelets, stimulated with thrombin or ADP, was not only accompanied by a 70% decrease in antifibrinogen antibody binding, but also an inability of EDTA or excess exogenous fibrinogen to dissociate more than half of platelet-associated fibrinogen, as well as the progressive association of bound fibrinogen with the platelet cytoskeleton. Costimulation of platelets with ZnCl2 and thrombin or ZnCl2 and ADP enhanced overall fibrinogen binding but not the EDTA-resistant component, and prevented the recovery of irreversibly bound fibrinogen with the Triton X-100 insoluble cytoskeleton. Costimulation of PMA- or Zn2+-treated platelets with low doses of A23187, however, restored the stabilization of platelet-fibrinogen interactions. These data suggest that modulation of bound fibrinogen expression on stimulated platelets can occur independently of the development of EDTA-resistant fibrinogen binding, and that stabilization of platelet-fibrinogen interactions is sensitive to stimulation-specific intracellular signal transduction.